CONTENT AND ORGANIZATION OF SPEECH THERAPY CLASSES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article analyzes the content, purpose and organizational features of speech therapy classes from a scientific and pedagogical point of view. The study highlights the main directions of speech therapy classes with children with speech disorders, their planning and effective organization methods. It also highlights the importance of articulation exercises, breathing exercises, the development of phonemic hearing, increasing vocabulary and the formation of coherent speech in classes.